2022
DOI: 10.1093/jas/skac009
|View full text |Cite
|
Sign up to set email alerts
|

Development of genomic predictions for Angus cattle in Brazil incorporating genotypes from related American sires

Abstract: Genomic prediction has become the new standard for genetic improvement programs, and currently, there is a desire to implement this technology for the evaluation of Angus cattle in Brazil. Thus, the main objective of this study was to assess the feasibility of evaluating young Brazilian Angus (BA) bulls and heifers for 12 routinely recorded traits using single-step genomic BLUP (ssGBLUP) with and without genotypes from American Angus (AA) sires. The second objective was to obtain estimates of effective populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 53 publications
0
6
2
Order By: Relevance
“…These results confirm that the use of large reference populations enables to achieve high weaning weight accuracies for both direct and maternal EBV in young animals. In contrast with the results of our study, both Jang et al [ 67 ] and Campos et al [ 66 ] reported values of dispersion for weaning weight that were mostly within the 0.85–1.15 interval, except for pedigree evaluations of total maternal in Campos et al [ 66 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These results confirm that the use of large reference populations enables to achieve high weaning weight accuracies for both direct and maternal EBV in young animals. In contrast with the results of our study, both Jang et al [ 67 ] and Campos et al [ 66 ] reported values of dispersion for weaning weight that were mostly within the 0.85–1.15 interval, except for pedigree evaluations of total maternal in Campos et al [ 66 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In ssSNPBLUP NAT , was on average 0.31 for direct EBV (ranging from 0.25 for CZE to 0.38 for CHE) and 0.21 for maternal EBV (ranging from 0.17 for CZE to 0.27 for CHE) (Table 7 ). In Brazilian Angus, Campos et al [ 66 ] conducted pedigree and genomic evaluations for growth traits using ssGBLUP [ 7 , 8 ] with about 1600 genotyped animals. For weaning weight gain, the average across validation groups was 0.39 for direct effect and 0.30 for total maternal (weaning weight and tick count) for PBLUP, and 0.45 for direct effect and 0.37 for total maternal for ssGBLUP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our values are in agreement to those of these authors for countries like CHE and smaller for other countries like CZE. Differences with our study could be due to the usage of a multi-variate model in combination with other growth traits (birth weight and post-weaning weight) in Campos et al (2022) as well as differences in population structure and trait definition. Recently, Jang et al (2022) reported LR estimates for genomic predictions of weaning weight in American Angus using a large reference population of about 180,000 genotyped animals and over 2,4 million weaning weight phenotypes.…”
Section: Benefits Of International Single-step Genomic Evaluationsmentioning
confidence: 72%
“…In ssSNPBLUP NAT , 𝑎𝑎𝑎𝑎𝑎𝑎𝑎𝑎𝑎𝑎𝑎𝑎 � � was on average 0.31 for direct EBV (ranging from 0.25 of CZE to 0.38 of CHE) and 0.21 for maternal EBV (ranging from 0.17 of CZE to 0.27 of CHE) (Table 5.7). In Brazilian Angus, Campos et al (2022) conducted pedigree and genomic evaluations for growth traits using ssGBLUP (Christensen and Lund 2010;Aguilar et al 2010) with about 1,600 genotyped animals. For weaning weight gain, the average 𝑎𝑎𝑎𝑎𝑎𝑎𝑎𝑎𝑎𝑎𝑎𝑎 � � across validation groups was 0.39 for direct effect and 0.30 for total maternal (weaning weight and tick count) for PBLUP, and 0.45 for direct effect and 0.37 for total maternal for ssGBLUP.…”
Section: Benefits Of International Single-step Genomic Evaluationsmentioning
confidence: 99%